The Use of Vlog-Making to Encourage Passive Students to Speak English - Ingkeatubun, Kethrin; Widiastuti, Oktavia; Muzammil, Lasim (Journal of English Language and Education, 2026)
Speaking skill development is a crucial goal in EFL instruction, yet many junior secondary school students remain passive due to anxiety and fear of negative evaluation. Previous studies have widely examined public video-based tasks, while the use of private vlog-making for passive learners has received limited attention. This study aims to investigate the use of private vlog-making as a pedagogical strategy to encourage passive students to speak English more confidently and actively. Employing a qualitative descriptive design, the study was conducted at a public junior secondary school in Malang involving ten ninth-grade passive students who produced two private vlogs over three weeks. Data were collected through vlog recordings, semi-structured interviews, and classroom observations, and analyzed using thematic analysis. The findings indicate that private vlog-making enhances psychological safety, supports repeated speaking practice, increases confidence, and encourages classroom participation. The study concludes that private vlog-making is an effective and supportive approach for promoting speaking development among passive EFL learners.